Simulasi Sistem Monitoring Kondisi Pasien Serangan Jantung Menggunakan Arduino dan Sensor Detak Jantung - Whiliams; Sean Coonery Sumarta (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2022)
Coronary heart disease is the most common cause of death in developed countries. The number of sufferers of this disease is increasing every year, WHO data states that 17.3 million people are estimated to die from cardiovascular causes in 2008, representing 30% of all global deaths. From the death data, it is estimated that 7.3 million are caused by coronary heart disease. CHD is still difficult to detect by the public because heart rate measurements are still using tools that are not yet portable. Therefore, the need for a portable heart attack detection device. Based on the problems that have been described, the researcher will design a system that aims to help monitor cardiac arrest patients where in an emergency situation they can immediately perform first aid. Through the interview process and literature studies that have been carried out, the researchers have designed a simulation using the waterfall method and carried out implementation tests on Cardiologists. Based on the research that has been done and testing the program to doctors, it is concluded that the program is good enough, but if you want to implement it, use a more accurate sensor to determine your heart rate when you are having a heart attack.